Processus de changement vers une nécessaire cohérence entre la gestion de la classe et la didactique des mathématiques dans un paradigme constructiviste - Dumouchel, Mélanie; Lanaris, Catherine (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This article presents, based on an analysis of the data collected as part of the first author’s doctoral research (Dumouchel, 2017), a description of the paths of three teachers engaged in a process of change (Collerette et al., 2013) towards appropriating a coherent link between the constructivist approach in the teaching of mathematics and classroom management. The article ends by examining the role of accompaniment as a condition facilitating the appropriation of this change towards a coherent relationship. Keywords: classroom management, didactics of mathematics, constructivist, change, coherence